Inside out 2 [videorecording (Blu-Ray + DVD)] - Mann, Kelsey; LeFauve, Meg; Holstein, Dave (Walt Disney Pictures, 2024)
The little voices inside Riley's head know her inside and out - but everything changes with the introduction of a new emotion: Anxiety, who has brought her friends for an extended stay.